2018
DOI: 10.3390/foods7010005
|View full text |Cite
|
Sign up to set email alerts
|

Protein Determination—Method Matters

Abstract: The reported protein content of foods depends on the analytical method used for determination, making a direct comparison between studies difficult. The aim of this study was to examine and compare protein analytical methods. Some of these methods require extraction preceding analysis. The efficacy of protein extraction differs depending on food matrices and thus extraction yield was determined. Overall, most analytical methods overestimated the protein contents. The inaccuracies were linked to indirect measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(217 citation statements)
references
References 28 publications
1
165
0
9
Order By: Relevance
“…Most methods of protein analysis tend to overestimate the amount of protein, and the Food and Agriculture Organisation of the United Nations (FAO) recommended that total protein is established by amino acid analysis [108]. Thus, the total amino acid content can be taken as a reasonable indication of total protein.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
“…Most methods of protein analysis tend to overestimate the amount of protein, and the Food and Agriculture Organisation of the United Nations (FAO) recommended that total protein is established by amino acid analysis [108]. Thus, the total amino acid content can be taken as a reasonable indication of total protein.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%
“…The Kjeldahl method is widely known and the most utilized method for total protein analysis in food (e.g. Moore et al 2010, Maehre et al 2018). There are numerous method standards for it and food and feed legislation often demands its use.…”
Section: Introductionmentioning
confidence: 99%
“…The Kjeldahl method is used to determine not only the protein component but also the relative nitrogen component, such as nitrate, ammonia, urea, nucleic acids, free amino acids, chlorophylls and alkaloids, all of which contain nitrogen [11]. The Bradford method is routinely used to determine the soluble protein content [21]. In the present study, the TNN content showed a weak negative correlation with the TSP content, and the TNN and TSP contents reached a peak in the tillering and booting stages, respectively.…”
Section: Discussionmentioning
confidence: 99%